Reimagining Admissions to Realize Equity in Teacher Education Programs - Hibbert, Kathyrn; Friesen, Deanna; Cole, Rebecca; Ott, Mary; Rouse, Janelle; Michaud, Robyn; Chen, Yi; Hobbs, Kevin (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Faculties of Education make important decisions about who our next generation of teachers will be. While universities have been making declarations of commitment to equity, diversity, and inclusion (EDI) principles, there is little alignment between their stated goals and their admissions practices. This study examined the relationship between two metrics intended to identify strong teacher candidates (i.e., experience profile scores and Computer-Based Assessment for Sampling Personal Characteristics (CASPer) z scores) to determine whether they identify the same candidates. The second goal was to examine the relative contributions of our admission criteria to our decision-making process. Data from 3017 teacher education applicants were analyzed. All variables were unique and significant predictors of admission status. Poor agreement was observed between the two admission metrics. However, the CASPer data addressed non-cognitive metrics and identified who was more likely to struggle in the program. We used this data to reimagine our admissions process, creating a more just and equitable system.